2003
DOI: 10.1152/jn.01147.2002
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Motor and Visual Information in the Parietal Area 5 During Locomotion

Abstract: The parietal cortex receives both visual- and motor-related information and is believed to be one of the sites of visuo-motor coordination. This study for the first time characterizes integration of visual and motor information in activity of neurons of parietal area 5 during locomotion under conditions that require visuo-motor coordination. The activity of neurons was recorded in cats during walking on a flat surface-a task with no visuo-motor coordination required (flat locomotion), walking along a horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 57 publications
(23 reference statements)
0
48
1
Order By: Relevance
“…Recent studies have reported a role of the parietal cortex of the cat during complex walking and reaching tasks (Fabre and Buser, 1981;Beloozerova and Sirota, 2003;, so it is reasonable to consider whether the loss of memory after a lesion in area 5 is attributable to a disruption of neuronal systems involved in the basic motor control of stepping over obstacles in the absence of delays. We believe this to be unlikely.…”
Section: Role Of the Parietal Cortex In Memoryguided Hindleg Movementsmentioning
confidence: 99%
“…Recent studies have reported a role of the parietal cortex of the cat during complex walking and reaching tasks (Fabre and Buser, 1981;Beloozerova and Sirota, 2003;, so it is reasonable to consider whether the loss of memory after a lesion in area 5 is attributable to a disruption of neuronal systems involved in the basic motor control of stepping over obstacles in the absence of delays. We believe this to be unlikely.…”
Section: Role Of the Parietal Cortex In Memoryguided Hindleg Movementsmentioning
confidence: 99%
“…The database for this study was a subset from the databases used for our previously published studies [6,7,8,9,49,50,60]. The selection of the neurons and neuronal populations for this study was based on the duration of available spike trains (4000-65000 spikes).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures of surgical preparation of the animals were described previously [7,50,52]. Surgery was performed under isoflourane (cats, 2-5%), halothane (cats, 1-2%), or pentobarbital sodium (rabbits, 25-35 mg/kg) anesthesia using aseptic procedures.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 2 more Smart Citations